Sex Difference of Type 2 Diabetes Affected by Abdominal Obesity versus Overall Obesity - Paek, Kyung-Won (Yonsei University College of Medicine, 2010)
PURPOSE: This research compares the predictive value of the abdominal obesity indicator, waist circumference (WC), and the overall obesity indicator, body mass index (BMI), among men and women with regard to type 2 diabetes. MATERIALS AND METHODS: This study used data collected from 4,400 households selected by a stratified multistage probability sampling method during the 2001 Korea National Health and Nutrition Examination Survey (KNHANES). The final study sample included 4,684 subjects over 30 years of age who had completed the health examination required for the analysis of the health interview and health behavior surveys. RESULTS: Both men and women showed significant differences in fasting blood glucose (FBG) or HbA1c levels based on abdominal obesity irrespective of BMI. However, the presence of overall obesity among men with abdominal obesity was not significantly correlated with FBG or HbA1c levels, while the presence of overall obesity among women with abdominal obesity was significantly different in regard to FBG or HbA1c levels. CONCLUSION: Both WC and BMI emerged as a measures of risk factors for type 2 diabetes among women while only WC emerged as a risk factor for diabetes among men.